2020
DOI: 10.1002/ehf2.13124
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure in the last year: progress and perspective

Abstract: Research about heart failure (HF) has made major progress in the last years. We give here an update on the most recent findings. Landmark trials have established new treatments for HF with reduced ejection fraction. Sacubitril/valsartan was superior to enalapril in PARADIGM‐HF trial, and its initiation during hospitalization for acute HF or early after discharge can now be considered. More recently, new therapeutic pathways have been developed. In the DAPA‐HF and EMPEROR‐Reduced trials, dapagliflozin and empag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 316 publications
(584 reference statements)
0
47
0
4
Order By: Relevance
“…Circulating microRNAs are small non-coding RNAs that influence protein translation and has gained much interest as potential genomic biomarkers. Their evaluation could help with the differentiation of the etiology behind heart failure (ischemic vs. nonischemic) and possibly with the prediction of the future course of the disease [ 87 , 88 ]. Although current evidence is lacking, there are some small studies that discovered high plasma levels of miRNA-16 in patients with ischemic and familial dilated cardiomyopathy, confirming its relationship with these etiologies [ 89 , 90 , 91 ].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Circulating microRNAs are small non-coding RNAs that influence protein translation and has gained much interest as potential genomic biomarkers. Their evaluation could help with the differentiation of the etiology behind heart failure (ischemic vs. nonischemic) and possibly with the prediction of the future course of the disease [ 87 , 88 ]. Although current evidence is lacking, there are some small studies that discovered high plasma levels of miRNA-16 in patients with ischemic and familial dilated cardiomyopathy, confirming its relationship with these etiologies [ 89 , 90 , 91 ].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…The cardioprotective effects of the SGLT2 inhibitors extend beyond glycemic control in patients with HF [ 12 , 24 ]. The metabolic impact of these agents are associated with the elevation of ketone body production, activation of anti-inflammatory and antioxidative pathways, and reduction of advanced glycation end-products mediated effects [ 24 , 25 ] Therefore, the mechanism of action of the SGLT2 inhibitors is complex and multifactorial [ 12 , 25 ]. While these findings justify the administration of SGLT2 inhibitors for patients with HFrEF and diabetes, recent trials reported comparable benefits in nondiabetic HF patients [ 10 ].…”
Section: Reviewmentioning
confidence: 99%
“…DAPA‐HF is the primary trial proving a critical advantage of dapagliflozin in HFrEF with a significant drop in hospitalizations due to the cardiovascular complications and exacerbation of heart failure amongst patients with HFrEF (HR 0.74; 95% CI 0.65-0.85) [ 25 ]. The analysis of the DAPA-HF trial has shown the benefits of dapagliflozin in mitigating the risk of heart failure progression and cardiac mortality, emphasizing the importance of early therapy initiation in all hospitalized patients with HFrEF [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что оптимальные концентрации натрийуретических пептидов (НУП) для диагностики ОДСН у пациентов с острой одышкой в отделении неотложной помощи выше по сравнению с теми, которые используются для диагностики хронической сердечной недостаточности (ХСН) у пациентов с одышкой при физической нагрузке в амбулаторных условиях, и зависят от возраста [4].…”
Section: Relationships Andunclassified